2022
DOI: 10.1007/s13593-022-00763-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a management strategy based on the relationships between brown rot and codling moth in two apple production systems

Abstract: Brown rot (BR) in relation to codling moth damage (CMD) is a key issue in apple production but the impact of these pests has not been assessed jointly. In addition, categorising cultivar reaction to these two pests for sustainable production systems could be essential for improving pest management. Therefore, in a 12-year study, 27 apple cultivars (9 scab-resistant, 9 commercial, and 9 old) were assessed for their reactions to BR in relation to CMD in integrated and organic production systems, and classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In this 5-year study, we determined the yield amount, yield classification categories, costs, annual revenues and income surplus or deficit The differences in yield and disease/pest damage between integrated and organic management systems were extensively documented in previous studies and it was concluded that the production risk was higher in the organic orchards than in the integrated ones (e.g. Holb et al, 2012Holb et al, , 2017Holb et al, , 2022Reganold et al, 2001). Relatively few studies evaluated the differences in cost, income and revenue among various apple management systems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In this 5-year study, we determined the yield amount, yield classification categories, costs, annual revenues and income surplus or deficit The differences in yield and disease/pest damage between integrated and organic management systems were extensively documented in previous studies and it was concluded that the production risk was higher in the organic orchards than in the integrated ones (e.g. Holb et al, 2012Holb et al, , 2017Holb et al, , 2022Reganold et al, 2001). Relatively few studies evaluated the differences in cost, income and revenue among various apple management systems (e.g.…”
Section: Discussionmentioning
confidence: 99%